Upaya BNP2TKI Dalam Menaggulangi Human Trafficking TKI di Malaysia Tahun 2010-2013 - Wijaya, Chandra Kusuma; Putranti, Ika Riswanti; Susiatiningsih, Hermini (Journal of International Relations, 2018)
The theme of this research is the effort and effectiveness of BNP2TKI role in Preventing Human Trafficking TKI in Malaysia 2010-2013. This research uses the concept of human trafficking to describe human trafficking of Indonesian migrant workers in Malaysia. This research, found that the efforts of BNP2TKI in preventing human trafficking of Indonesian migrant workers in Malaysia 2010-2013 are conducted by advocacy and law enforcement, labor protection in pre-placement, placement and post-placement period. In addition, BNP2TKI conducted computerization, as well as coordination with domestic agencies and cooperation with various international actors, including INCB, ILO and IOM. The role of BNP2TKI in dealing with Indonesian human trafficking issues in Malaysia has shown good achievement, although it can not be a fundamental solution. This is marked by decrease in cases, optimization of service standardization to system automation.